Non-surgical management of advanced ovarian cancer with maintenance PARP inhibitors - Taliya Lantsman; Lily Jia; Meghan Shea (Elsevier, 2024)
The standard of care for advanced ovarian cancer is cytoreductive surgery followed by a platinum-taxane combination with PARP inhibition as a maintenance strategy. In practice, many advanced ovarian cancer patients are older and are either not candidates for surgery or decline surgical intervention. There are limited data for using PARP inhibitor maintenance in the non-surgical patient population. We describe two cases of patients with advanced-stage ovarian cancer who received platinum-taxane chemotherapy and declined surgical debulking. They were continued on maintenance PARP inhibitors and have no evidence of disease for over four years.